INVESTASI DAN LIFESTYLE INVESTOR PEREMPUAN DI PASAR MODAL SYARIAH SUMATERA SELATAN - lemiyana lemiyana (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
This study aims to determine the effect of investment and the lifestyle of female investors in Islamic capital market South Sumatra. The research method used is exploratory research, where the variables are measured by a Likert scale. The data collection method was carried out by interview (interview), with a questionnaire and documentary study. Data processing using Structural Equation Model (SEM) software. The results showed that (1) investment has a positive and significant impact on female investors in Islamic capital market South Sumatra (2) Lifestyle affects modern female investors in Islamic capital market South Sumatra.